A Systematic Review of Factors that Influences the Efficacy of Computer Based Learning - Segun Emmanuel Adewoye; Abayomi Oladele Olaseni (JETL (Journal of Education, Teaching and Learning), 2022)
Despite emerging evidence from research studies showing positive influence of computer based learning on quality of education and academic achievement of learners, there is very limited research studies that synthesises factors that influence or contributes to the success or effectiveness of computer based learning methods. The purpose of this systematic review was to synthesise factors that influences the efficacy of computer based learning. We followed the protocol from preferred reporting items for systematic reviews and meta-analyses (PRISMA). Major electronic educational databases were searched. In total, 20 studies that met inclusion criteria were reviewed in this study. After completing thematic analysis of the included studies, findings revealed that students’ characteristics factor such as attitudes, self-discipline, prior knowledge of computer use and motivation, also infrastructure factor such as easy access to computer and availability of technology influenced the efficacy of Computer Based Learning. Recommendations from the research reports are discussed.